A New Manifestation of American Socially Engaged Fiction - Magdalena Bazylewicz (European Journal of American Studies)
The article addresses a peculiar manifestation of the contemporary American socially engaged novel: the PEN/Bellwether Prize for Socially Engaged Fiction. Using the tools of the New Historicism, the work scrutinizes Ron Childress’ award-winning novel And West is West in an attempt to establish what it means for a modern work fiction to be socially engaged. Through creative application of Foucault’s discourse analysis intertwined with AnisShivani’s theory of plastic realism, the paper analyses the cultural forces at play in a self-proclaimed novel of social reform.